2010
DOI: 10.1063/1.3428470
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance and magneto-optical enhancement on Au–Co nanocomposite thin films

Abstract: We present our investigations on the enhancement of magneto-optical (MO) effects in nanocomposite Au–Co thin films. All the samples in this study were obtained by cosputter deposition varying the relative Au:Co composition and the growth temperature. A strong enhancement of the transverse MO activity is observed when surface plasmons are excited in the Kretschmann configuration. The correlation between the nanocomposite films' microstructure, morphology, composition, and their optical response under surface pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…More recently, a deeper analysis of this kind of systems has been carried out, focused mainly in the transversal confi guration, where the plasmon excitation, [ 131 ] the dependence on the ferromagnetic layer thickness [ 132 ] and its position within the layer, [ 78,133,134 ] the nature of the plasmonic material, [ 135,136 ] the crystalline and interface quality, [ 137 ] have been studied in a series of noble metal/ferromagnetic/noble metal trilayer structures or nanocomposite [ 138,139 ] thin fi lms. For example, Figure 11 shows how both the refl ectivity (which is related to the SPP excitation quality) and the purely MO component, ΔR pp here, can be optimized by appropriate choice of the layer thicknesses to obtain the desired MO enhancement.…”
Section: Continuous Layersmentioning
confidence: 99%
“…More recently, a deeper analysis of this kind of systems has been carried out, focused mainly in the transversal confi guration, where the plasmon excitation, [ 131 ] the dependence on the ferromagnetic layer thickness [ 132 ] and its position within the layer, [ 78,133,134 ] the nature of the plasmonic material, [ 135,136 ] the crystalline and interface quality, [ 137 ] have been studied in a series of noble metal/ferromagnetic/noble metal trilayer structures or nanocomposite [ 138,139 ] thin fi lms. For example, Figure 11 shows how both the refl ectivity (which is related to the SPP excitation quality) and the purely MO component, ΔR pp here, can be optimized by appropriate choice of the layer thicknesses to obtain the desired MO enhancement.…”
Section: Continuous Layersmentioning
confidence: 99%
“…4 Recently, it has also been reported that the MO effect is enhanced in nanostructures consisting of MTMs and NMs due to localized surface plasmon resonance (LSPR). [5][6][7][8] In addition to a large MO effect, perpendicular magnetic anisotropy is a prerequisite for applications such as highdensity magnetic and MO recording media, 9 high-resolution MO SLMs, 10,11 and spin electronics devices. 12,13 Co-Pt alloys, multilayers, and nanostructures that exhibit a relatively large MO effect at shorter blue light wavelengths are potentially useful for these applications because of their large perpendicular magnetic anisotropy and good chemical stability.…”
mentioning
confidence: 99%
“…Nevertheless, they have large MO constants. There have been several approaches to reach the best magnetoplasmonic system such as noble metal/ferromagnetic metal multilayer structures, [9][10][11][12] noble metal/ferromagnetic metal nanocomposite thin films, 13 or noble metal/ferromagnetic dielectric structures. [14][15][16][17][18] Also systems consisting of magnetic nanoparticles (NPs) embedded in a dielectric matrix, 19,20 as well as noble metal-ferromagnetic metal nanostructures in a dielectric matrix have been studied to obtain ferromagnetism and plasmonics together.…”
mentioning
confidence: 99%